Utility of tissue Doppler imaging in predicting outcome in patients with idiopathic pulmonary fibrosis. - Pitsiou, G; Papadopoulos, C; Karvounis, H; Karamitsos, T; Giannakoulas, G; Efthimiadis, G; Kontakiotis, T; Argiropoulou, P; Parharidis, G (2007)
BACKGROUND: There are limited reports in the literature concerning right ventricular (RV) performance in patients with non end-stage idiopathic pulmonary fibrosis (IPF) who exhibit mild to moderate pulmonary hypertension (PH). We evaluated RV functional impairment in such a cohort using both conventional echocardiography and tissue Doppler imaging (TDI) and in addition we assessed the association of specific TDI indices with survival. METHODS: Twenty-two clinically stable patients with non-end stage IPF and mild to moderate PH were assessed. Twenty-two healthy individuals served as controls. We evaluated RV systolic and diastolic function and further estimated peak pulmonary artery systolic pressure (PASP). In addition, by combining TDI and Doppler echocardiography, we calculated the ratio of trans-tricuspid E-wave velocity to early diastolic tricuspid annulus velocity (RV E/Em). Patients were followed for a median period of 22 months and the incidence of death was recorded. RESULTS: Both echocardiographic modalities revealed impaired RV systolic and diastolic function in the IPF group compared to controls. A significant negative correlation was observed between RV E/Em and PASP (r = -0.5, p = 0.018). The probability of survival was 54.5% for those patients with RV E/Em < 4.7 versus 100% for those with an index > 4.7 (log-rank statistic 5.81, p = 0.016). CONCLUSIONS: TDI modality may serve as an alternative to conventional ultrasound technique for risk stratification and PH estimation in non end-stage IPF patients.